Tracking Conformational Changes in Calmodulin in vitro, in Cell Extract, and in Cells by Electron Paramagnetic Resonance Distance Measurements. Issue 14 (26th June 2019) - Dalaloyan, Arina; Martorana, Andrea; Barak, Yoav; Gataulin, Diana; Reuveny, Eitan; Howe, Andrew; Elbaum, Michael; Albeck, Shira; Unger, Tamar; Frydman, Veronica; Abdelkader, Elwy H.; Otting, Gottfried; et al.
Abstract: It is an open question whether the conformations of proteins sampled in dilute solutions are the same as in the cellular environment. Here we address this question by double electron‐electron resonance (DEER) distance measurements with Gd(III) spin labels to probe the conformations of calmodulin (CaM) in vitro, in cell extract, and in human HeLa cells. Using the CaM mutants N53C/T110C and T34C/T117C labeled with maleimide‐DOTA‐Gd(III) in the N‐ and C‐terminal domains, we observed broad and varied interdomain distance distributions. The in vitro distance distributions of apo ‐CaM and holo ‐CaM in the presence and absence of the IQ target peptide can be described by combinations of closed, open, and collapsed conformations. In cell extract, apo ‐ and holo ‐CaM bind to target proteins in a similar way as apo ‐ and holo ‐CaM bind to IQ peptide in vitro . In HeLa cells, however, in the presence or absence of elevated in‐cell Ca 2+ levels CaM unexpectedly produced more open conformations and very broad distance distributions indicative of many different interactions with in‐cell components. These results show‐case the importance of in‐cell analyses of protein structures. Abstract : Double electron‐electron resonance distance measurements of calmodulin with Gd(III) spin labels reveal different conformations and conformational changes in HeLa cells compared to in vitro measurements and studies on HeLa cell extracts.